Młodzież wobec wartości - Błasiak, Anna (Horyzonty Wychowania, 2017)
The aim of the article was to show specific knowledge ofyoung people and their world of values, whose original objectiveis to serve educational work. Adolescence is the time in which theprocesses of creating individual value system and shaping viewpointtake place. Educational support is essential in this periodsince despite profound sensitivity to values, discovering valuesby a young person does not necessarily lead to identification withthem. Beside theoretical investigation, the article includes conclusionsresulting from the study conducted by the authorconcerning values adopted and realized by young people.Questions regarding values of the young generation remainup-to-date and significant since they exhibit both social (youngpeople are the future of the society and its chance) and individualcharacter (values influence the shape and quality of man’s life).